Development of novel peptide-based Michael acceptors targeting rhodesain and falcipain-2 for the treatment of neglected tropical siseases (NTDs) - Previti, Santo; Ulrich, Kathrin; Krauth-Siegel, Renate (Journal of medicinal chemistry, 2017)
This paper describes the development of a class of peptide-based inhibitors as novel antitrypanosomal and antimalarial agents. The inhibitors are based on a characteristic peptide sequence for the inhibition of the cysteine proteases rhodesain of Trypanosoma brucei rhodesiense and falcipain-2 of Plasmodium falciparum. We exploited the reactivity of novel unsaturated electrophilic functions such as vinyl-sulfones, -ketones, -esters, and -nitriles. The Michael acceptors inhibited both rhodesain and falcipain-2, at nanomolar and micromolar levels, respectively. In particular, the vinyl ketone 3b has emerged as a potent rhodesain inhibitor (k2nd = 67 × 106 M-1 min-1), endowed with a picomolar binding affinity (Ki = 38 pM), coupled with a single-digit micromolar activity against Trypanosoma brucei brucei (EC50 = 2.97 μM), thus being considered as a novel lead compound for the discovery of novel effective antitrypanosomal agents.
Gesehen am 25.09.2018